Injuries Among Sepak Takraw Players: The Relationship Between Training Patterns, Rest Duration, and Injury Severity - Nimrot Manalu; Miftahul Ihsan; Andes Martua Harahap; Mona Benedikta Ambarita; Dani Sembiring; Joison Situmorang; Ariska Br Sitepu; Bastian Lubis; Dodi Simanjuntak; Leo Renhard Purba (Ikatan Sarjana Olahraga Republik Indonesia (Kabupaten Kampar), 2025)
Objectives: Sepak takraw is a traditional Southeast Asian sport that combines elements of soccer and volleyball, requiring high levels of flexibility, agility, and coordination. Despite its growing popularity, limited research exists on injury patterns and their relationship with training variables among sepak takraw players. Methods: A cross-sectional study was conducted involving 210 sepak takraw players from seven clubs in Medan City, Indonesia. Data were collected through structured questionnaires and injury assessment forms over a 12-month period. Training patterns, rest duration, and injury severity were analyzed using quantitative methods. Results: The study revealed that 68.5% of participants experienced at least one injury during the observation period. Lower extremity injuries were most common (72.3%), followed by upper extremity injuries (18.9%). Players with inadequate rest periods (<48 hours between intensive training sessions) showed significantly higher injury rates (p<0.001). Training frequency exceeding 5 sessions per week was associated with increased injury severity (OR=2.34, 95% CI: 1.45-3.78). Conclusion: Training patterns and rest duration significantly influence injury occurrence and severity in sepak takraw players. Implementing structured rest periods and optimized training schedules may reduce injury risk and enhance player safety.